2008
DOI: 10.1002/ibd.20354
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D derivatives induce apoptosis and downregulate ICAM-1 levels in peripheral blood mononuclear cells of inflammatory bowel disease patients

Abstract: 1,25(OH)2D3 and EB 1089 inhibit PBMC proliferation, induce apoptosis in PBMC of healthy subjects and IBD patients, and affect ICAM-1 expression on PBMC and on HUVEC cocultured with PBMC, suggesting that the ICAM-1 downregulation could provide a new target for controlling the recruitment of leukocytes at the sites of inflammation in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…More recently, it has been reported that vitamin D may be used as a therapeutic option to treat inflammatory diseases, including Behç et's disease, inflammatory bowel disease, multiple sclerosis, experimental sepsis and inflammatory polyarthritis [27][28][29][30][31][32][33]. IVIG therapy has been reported to be effective for reducing the incidence of coronary artery lesions in KD patients [34][35][36].…”
Section: Discussionmentioning
confidence: 98%
“…More recently, it has been reported that vitamin D may be used as a therapeutic option to treat inflammatory diseases, including Behç et's disease, inflammatory bowel disease, multiple sclerosis, experimental sepsis and inflammatory polyarthritis [27][28][29][30][31][32][33]. IVIG therapy has been reported to be effective for reducing the incidence of coronary artery lesions in KD patients [34][35][36].…”
Section: Discussionmentioning
confidence: 98%
“…TNF-a has been shown to enhance LFA-1 expression 22 and IFX has been shown to reduce expression of the ligand of LFA-1 (ICAM-1) and CD40 ligands on T cells. [23][24][25] Because IFX suppresses activated effector cells through apoptosis or antibody-dependent cytotoxicity, 26 the decrease in LFA-1 expression found in our investigation seems to be a consequence of a decrease in the number of activated T cells and leukocytes that express LFA-1. It is well known that among the subsets of T cells, LFA-1 expression is increased in CD4þ and CD8þ T cells in patients with CD.…”
Section: Discussionmentioning
confidence: 57%
“…22,23 Parenterally fed animals show significantly less MAdCAM-1 expression and messenger RNA in PP. 38,39 Because some vitamins reportedly alter gene expression of adhesion molecules, 40,41 PQQ might also have upregulated MAdCAM-1 expression on PP endothelial cells. In contrast, PN does not induce depletion of MAdCAM-1 expression in the small intestine except in PP.…”
Section: Discussionmentioning
confidence: 99%